2015
DOI: 10.3899/jrheum.141054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Serological Analysis of Patients with Positive Anticyclic Citrullinated Peptide Antibodies Referred Through a Rheumatology Central Triage System

Abstract: About 58% of patients with a positive ACPA referred through a triage system for a rheumatologist opinion received a diagnosis of RA at their first visit. RF provides additional useful information to guide the diagnosis and urgency of referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The specificity of detection of anti-CarP antibodies is similar to IgM-RF and is slightly lower than anti-CCP2 antibodies. Even though anti-CCP2 antibodies and IgM-RF are both part of the 2010 classification criteria, individuals positive for these autoantibodies are also identified in the non-RA arthritis groups, as has also been reported before [ 15 17 ]. Therefore, it may not be surprising that anti-CarP antibodies, not being part of the 2010 classification criteria, can also be present in arthritic conditions other than RA.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The specificity of detection of anti-CarP antibodies is similar to IgM-RF and is slightly lower than anti-CCP2 antibodies. Even though anti-CCP2 antibodies and IgM-RF are both part of the 2010 classification criteria, individuals positive for these autoantibodies are also identified in the non-RA arthritis groups, as has also been reported before [ 15 17 ]. Therefore, it may not be surprising that anti-CarP antibodies, not being part of the 2010 classification criteria, can also be present in arthritic conditions other than RA.…”
Section: Discussionsupporting
confidence: 60%
“…In the current study, we observed that anti-CarP antibodies occur in almost all forms of early arthritis. Although at lower frequencies, anti-CCP antibodies were also detected in many other forms of arthritis (Table 2 ) [ 15 17 ]. Whether or not anti-CarP-positive patients with diagnoses other than RA have a different disease course than the anti-CarP-negative patients with the same diagnosis is a subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[22] In addition, the CReATe Rheum system has provided a novel opportunity to perform quality assurance analyses of various diagnostic services and the utilization of selected biomarkers to assist in the triage process [23,24]. Page 14 Our evaluation was limited by the pre-/post-study design.…”
Section: Page 13mentioning
confidence: 99%